THE SOCIAL CONSTRUCTION OF REALITY, TRAUMA, AND IDENTITY IN DONNA TARTT’S THE GOLDFINCH - S. Sivaranjini (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study examines the social construction of reality in Donna Tartt’s The Goldfinch, focusing on how individuals and societies create meaning through trauma, art, relationships, and cultural contexts. It aims to analyze how Theo Decker’s life is shaped by the traumatic loss of his mother and his possession of The Goldfinch, a priceless painting that becomes both a physical and symbolic anchor for his identity, guilt, and longing. The study explores the contrasting social environments in the novel—from the sophisticated art world of New York to the morally ambiguous landscape of Las Vegas—and how these contexts influence Theo’s perception of reality. Key relationships with characters such as Boris, Hobie, and Pippa are examined to demonstrate the fluidity and subjectivity of identity and meaning. Tartt’s portrayal of the art world is analyzed to uncover how society assigns value and constructs shared realities, with The Goldfinch symbolizing humanity’s quest for beauty and purpose amidst chaos. Ultimately, the study concludes that Theo’s existential reflections highlight the tension between inherent meaning and socially constructed narratives. By intertwining personal trauma with broader cultural influences, The Goldfinch reveals the fragile and dynamic nature of human experience. The novel underscores how individuals navigate and reshape their realities through the interplay of art, loss, and love, offering profound insights into the construction of meaning in contemporary life.